The effect of problem-based learning (PBL) and audio-visual media on learning outcomes in social studies for junior high school students in Susukan District - Zwitsy Valentina Setiawan; Sudarno Sudarno; Khresna Bayu Sangka (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to determine the influence of the problem-based learning (PBL) model and audio-visual media on students’ learning outcomes in Social Studies (IPS) at the junior high school level in Susukan District. A causal quantitative method was employed using multiple linear regression analysis. The population consisted of 1,768 students from three schools: MTs Ma’arif NU 01 Susukan, SMP Negeri 1 Susukan, and SMP Negeri 2 Susukan. A total sample of 327 students was selected through Proportionate Stratified Random Sampling. Data were collected using a questionnaire. The results show that: (1) the PBL model has a positive but not significant effect on learning outcomes, indicated by a t-value of 1.671 < t-table 1.967 and a significance level of 0.096. Its contribution is relatively low, with an Effective Contribution (SE) of 1.4% and a Relative Contribution (SR) of 9%. (2) Audio-visual media has a positive and significant effect on learning outcomes, shown by a t-value of 4.817 > 1.967 and a significance level of 0.000. This variable contributes an SE of 14.2% and an SR of 91%. (3) Simultaneously, PBL and audio-visual media have a positive and significant effect on Social Studies learning outcomes, as evidenced by an F-value of 29.998 > F-table 3.023. The coefficient of determination (R²) of 15.6% indicates that both variables influence learning outcomes, although the effect is relatively weak, while the remaining 84.4% is influenced by other factors not examined in this study.